PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS MENGGUNAKAN MODEL PEMBELAJARAN PACE DENGAN KONTEKS KEMARITIMAN PADA SISWA KELAS VIII SMP - Nur Fitriani, Khofifah Intan; Alona Dwinata; Nurul Hilda Syani Putri (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2024)
This research was carried out to see the difference in improvement in students' mathematical reasoning abilities when the Project, Activity, Cooperative learning, Exercise (PACE) learning model was applied in a maritime context compared to conventional learning methods. This research used a quasi-experiment design on class VIII students at SMP Negeri 1 Bintan, covering classes VIIIA to VIIIH with sampling using cluster sampling techniques and it was found that class VIIIH was the class that received treatment or the experimental class and VIIIG was the control class. Data was collected through observation sheets. and a test of 5 questions in the form of questions describing tests of mathematical reasoning abilities. The results of data processing showed that students in the classes that received treatment had increased their mathematical reasoning abilities with an average increase of 0.378. In contrast, students in the control class had an average increase of 0.25. Based on this, it was found that students who were treated with the PACE learning model in the maritime context showed a higher increase in mathematical reasoning abilities compared to the conventional model.